A percepção da imagem do Instituto Federal Baiano no contexto do desenvolvimento local - NASCIMENTO, Valéria dos Santos (2016)
This research is originated from the following problem: how the image of the Instituto Federal Baiano is perceived by local actors. Its overall objective is to identify the contributions of the organizational image to the management of the Instituto Federal de Educação, Ciência e Tecnologia Baiano (IF Baiano). In this regard, this research draws on fieldwork in the cities of Catu and Teixeira de Freitas due to IF Baiano being a school originated from the old Escolas Agrotécnicas Federais (EAF) and Escolas Médias de Agropecuária Regional da Comissão Executiva do Plano da Lavoura Cacaueira (EMARC of CEPLAC), represented in the cities above. In the cities, the data collection was conducted by interviews on site with 34 local actors (managers and / or leaders of public, private and third sector agencies) and, subsequently, with 68 respondents by web form. In this research, it is considered the variable organizational image from the Image Configuration Method (ICM) by Schuler and De Toni (2015). The ICM analysis was configured into two phases: Content Configuration, with a qualitative approach, and Grouping Configuration bringing a quantitative approach. For the ICM, the methodology is Content Analysis. As main results, it is noticed that IF Baiano is seen as a quality educational institution that offers technical education. It also assists people in forming their principles and values, besides it changes their lives. Consequently, the local population is proud of having such an institution in their cities, besides they consider IF Baiano a place that receives the student community in a safe and happy environment. Finally, it is inferred that despite its positive image through local actors’ point of view, the Instituto Federal Baiano is not spreading the concept of a Federal Institution of Education, Science and Technology. Especially in aspects related to its purposes, characteristics and goals. As research finding, it is noticed that the community has a positive image and creates expectations regarding IF Baiano, although, the institution is not succeeding in achieving the established image described in its official documents.